2008
DOI: 10.1136/oem.2007.037689
|View full text |Cite
|
Sign up to set email alerts
|

Excess of mesotheliomas after exposure to chrysotile in Balangero, Italy

Abstract: The cluster of 14 mesothelioma cases among workers who were active in the mine and 13 among other people exposed to Balangero chrysotile provides further evidence that tremolite-free chrysotile is carcinogenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 17 publications
0
53
1
1
Order By: Relevance
“…We therefore applied the average 2000-2011 regional incidence rates calculated among subjects aged ≥70 years, which were 4.1 and 3.7 (×100,000 person-years). A similar approach was used in a study of MM incidence near an asbestos mine in Balangero, Piedmont, northern Italy (Mirabelli et al, 2008). For the population with environmental exposure while living in Broni, we used as reference the overall non-exposed rates (1.0 and 0.8 × 100,000 person-years in men and women, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore applied the average 2000-2011 regional incidence rates calculated among subjects aged ≥70 years, which were 4.1 and 3.7 (×100,000 person-years). A similar approach was used in a study of MM incidence near an asbestos mine in Balangero, Piedmont, northern Italy (Mirabelli et al, 2008). For the population with environmental exposure while living in Broni, we used as reference the overall non-exposed rates (1.0 and 0.8 × 100,000 person-years in men and women, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, a study using a similar approach evaluated the effect of occupational and nonoccupational exposure related to an asbestos mine in Balangero (closed in 1985) among mine workers (including clerical workers and employees of sub-contractors) and their family members, residents in proximity to the mine, and in other occupational groups that used or reused material from the mine (Mirabelli et al, 2008). Using data from the Piedmont mesothelioma registry, the authors found a much higher number of pleural MM cases (14 among mine workers and 13 among other people) in 1990-2001 than previously reported in a cohort study of miners (two cases as of 1987).…”
Section: Discussionmentioning
confidence: 99%
“…on the Wittenoom cohort studies seems to be compelling [81][82][83], although the number of deaths with mesothelioma in men in the period 1987 to 2008 remained similar to the lowest predictions (the number of Mt in the past 8 years was higher than predicted -74 vs. 63) [83], while genetic predisposition was discussed along with asbestos as an etiologic factor of Mt [84]. There is considerable evidence that the risk of Mt is enhanced after exposure to chrysotile without amphibole admixture [46,48,[72][73][74][75][76]85]. There has been also an alternate view [86,87] e.g.…”
Section: Page -02mentioning
confidence: 99%
“…In the author reply [71], the arguments from [67] have not been adequately responded, being dismissed by a declaration that the studies [68,69] "appear to support the concepts put forward by Bernstein et al" followed by self-references [71]. Other reports and reviews [43][44][45][46][47][48]51,56,58,63,[72][73][74][75], not supporting the authors' concept, are also not cited in the voluminous reviews [41,55]. Another example: Bernstein et al cite a rather nondescript phrase from the review "Mesothelioma from chrysotile asbestos" [55,76] that chrysotile is an "exclusive or overwhelming fiber exposure", disregarding the main conclusion: "Chrysotile asbestos, along with all other types of asbestos, has caused mesothelioma" [76].…”
Section: Page -02mentioning
confidence: 99%
“…These studies demonstrate that the so-called "controlled use" of asbestos is a fallacy [42]. Workers exposed to chrysotile fibers alone have excessive risks of lung cancer and excessive deaths from mesothelioma [43][44][45]. The Canadian Medical Association, the Canadian Cancer Society, and Canada's leading health experts oppose the export of asbestos to the developing countries.…”
Section: Chrysotile Asbestosmentioning
confidence: 99%